The Covid-19 pandemic and economic stimulus in India: has it been a hostage of macroeconomic complications?. Issue 6 (2nd November 2021) - Chakrabarty, Himadri Shekhar; Ray, Partha; Pal, Parthapratim
ABSTRACT: This paper analyzes the efficacy and skepticism surrounding the economic stimulus package announced by the Indian authorities in response to the Covid-19 pandemic in 2020. While the end of the pandemic is yet to be on the horizon, countries across the world have been undertaking economic stimulus packages of varied nature, depth, and quantum. A scrutiny of these packages show that India has been cautious in formulating policy measures and balancing inter-temporal objectives. The disaggregated economic stimulus package in India belies the justification of it being an adequate stimulus in managing the mammoth crisis, especially when the authorities had resorted to more deferred spending measures while the need of the hour was direct fiscal spending. Specifically, this study argues that the causes behind the fiscal conservativeness might be linked to India's twin deficits in the fiscal and current account fronts, along with the fear of a potential capital flight and a possible adverse response by the foreign investors.